STRATEGI PENGEMBANGAN DESA WISATA EKOLOGIS DI DESA JEMPANANG DI PETANG KABUPATEN BADUNG BALI - Kiskenda, Dewa; Nyoman Agus trimandala (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Ecotourism Jempanang Dalas is trying to encourage the number of tourist visits. However, tourist visits are still considered not optimal. This study discusses existing conditions and examines strengths and weaknesses as well as opportunities and threats to formulate strategies and programs for the development of Jempanang Dalas Ecotourism in Belok Sidan Village optimally and maintain its sustainability. This study uses a quantitative and qualitative approach. Data collection was carried out by observation, indepth interviews with Belok Sidan Village Head, Petang Subdistrict Jempanang Dalas ecotourism manager local traditional leaders. Then an analysis was carried out using the SWOT method. Based on the SWOT analysis, alternative strategies that can be applied to the development of Ecotourism in Japan Dalas were obtained, namely strategies for creating quality ecotourism products, strategies for increasing promotion through the application of information technology, strategies for developing human resource competencies and marketing strategy for ecotourism products for tourists who stay in villas and tourist attractions in Belok Sidan Village and its surroundings.